2014
DOI: 10.1136/oemed-2014-102304
|View full text |Cite
|
Sign up to set email alerts
|

Compensation benefits in a population-based cohort of men and women on long-term disability after musculoskeletal injuries: costs, course, predictors

Abstract: Knowing costs, duration and predictors of long-term compensation claims by gender can help employers, decision makers and rehabilitation specialists to identify at-risk workers and industries to engage them in early intervention and prevention programmes. Tailoring parts of long-term disability prevention and management efforts to men's and women's specific needs, barriers and vulnerable subgroups, could reduce time on benefits among both male and female long-term claimants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…There was a higher percentage of fall injuries that resulted in back injuries in Private SLE compared to Public SLE. Back injuries typically result in higher median costs per workers’ claim, and total costs for both genders, as well as longer compensation benefit duration (Lederer and Rivard 2014 ). Since back claims are so costly, ALJ adjudication may occur more often to resolve compensation monetary award disputes.…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher percentage of fall injuries that resulted in back injuries in Private SLE compared to Public SLE. Back injuries typically result in higher median costs per workers’ claim, and total costs for both genders, as well as longer compensation benefit duration (Lederer and Rivard 2014 ). Since back claims are so costly, ALJ adjudication may occur more often to resolve compensation monetary award disputes.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has identified that there are important differences in the work disability duration of men and women, evident in different likelihoods of injured workers returning to work [1], transitioning off disability benefits [2, 3], and transitioning onto permanent disability pension [46]. Understanding why differences may exist between men and women’s occupational health outcomes, such as work disability duration, is challenging due to the role of biological sex-based factors as well as more socially determined gender-based factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, administrative data were used to examine the likelihood of workers with long-term sickness absence (≥ 8 weeks) transitioning onto permanent disability to find that despite larger proportions of permanent disability among women (6.5%) than men (4.9%), there was no statistically significant difference after adjusting for confounders [4]. In Quebec, Canada, using administrative data, men and women transitioned off work disability benefits at a similar rate in the first 3-to-12 months but by the second and third years, the transition slowed more for men, resulting in a statistically significant shorter duration for women over the long term [2].…”
Section: Introductionmentioning
confidence: 99%
“…4 According to the United States Bureau of Labor Statistics, CTS accounted for the third highest number of median days away from work in 2013, behind only injuries involving fractures, 32 and is generally associated with significant costs to society and the health care system. 12,22 Carpal tunnel syndrome is frequently claimed to be an occupational disease, though studies have both supported and refuted this claim. 11,20,27,28 Workers' compensation (WC) patients who undergo carpal tunnel release (CTR) have been found to have poorer outcomes and delayed return to work (RTW) when compared with noncompensated patients in prior studies.…”
Section: Introductionmentioning
confidence: 99%